New Testosterone Derivatives as Semi-Synthetic Anticancer Agents Against Prostate Cancer: Synthesis and Preliminary Biological Evaluation - Morin, Nathalie; Bruneau, Julie; Fortin, Sebastien; Brasseur, Kevin; Leblanc, Valerie; Asselin, Eric; Berube, Gervais (Medicinal Chemistry, 2015)
Prostate cancer (PC) is a major health issue in the world. Treatments of localized PC are quite efficient and usually involve surgery, radiotherapy and/or hormonal therapy. Metastatic PC is however rarely curable to this day. Treatments of metastatic PC involve radiotherapy, chemotherapy and hormonal treatment such as orchiectomy, antiandrogens and luteinizing hormone-releasing hormone agonists. The suppression of tumor growth by hormonal treatment is efficient but overtime resistance still occurs and the disease progresses. Thus, more urgently than ever there is a need for discovery of new treatment options for castration-resistant PC (CRPC). Hence, we designed and tested a series of amide derivatives located at position 7α of testosterone as prospective “natural” or “semisynthetic” anticancer agents against CRPC with the goal of discovering therapeutic alternatives for the disease. This manuscript describes an efficient path towards the target molecules that are made in only 6 or 7 chemical steps from testosterone in good overall yields. This strategy can be used to make several compounds of interest that present higher biological activity than the classic antiandrogen; cyproterone acetate (3). The best testosterone-7α-amide was the N-2-pyridylethylamide (25) which was as active as the antiandrogen cyproterone acetate (3) on androgen-dependent LNCaP cells and 2.7 times more active on androgen-independent PC3 prostate cancer cells. The results obtained show the synthetic feasibility and the potential for future development of this unique class of semi-synthetic anticancer agents that offer the premise of new treatment modalities for patients afflicted with CRPC.
Keywords: Testosterone-7α-linked amides